The Effect of Managing Receivables and Inventory on Profitability: A Case Study of a Multifinance Company in Medan - Tantri Octora Dwi Syah Putri (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
This research aims to investigate the impact of accounts receivable management and inventory management on the profitability of a multi-finance company in Medan, both separately and together. The study employs a quantitative research approach, focusing on the financial reports of a selected multi-finance company in Medan. The sample includes income statements and balance sheets spanning twelve quarters. Data is collected through both primary and secondary sources, including interviews and observations. The analysis reveals that, when considered simultaneously, both accounts receivable management and inventory management significantly affect profitability, with a determination value of 82.2%. Specifically, accounts receivable management independently contributes to profitability, as does inventory management. These findings have crucial implications for financial management practices within organizations. By highlighting the importance of effective accounts receivable and inventory management, companies can enhance their financial performance, emphasizing the need for strategic approaches in these areas. This research underscores the necessity for multi-finance companies to develop and implement robust management practices to achieve long-term financial stability and growth. Future research should explore the impact of technology on these management practices to further refine strategies for maximizing profitability. In conclusion, focusing on optimizing accounts receivable and inventory management not only improves profitability but also establishes a solid framework for sustainable business success in a competitive financial landscape.